Product innovation in emerging market-based international joint ventures: An organizational ecology perspective - Zhou, Changhui; Li, Jing (Journal of International Business Studies, 2008)
This study investigates product innovation in market-seeking international joint ventures (IJVs) in a large emerging market, and tests two sets of hypotheses: organizational orientation and environmental adaptation. Drawing on organizational ecology theory, we suggest that IJVs’ product innovation can be understood as a consequence of organizational orientation defined by IJV contract specifications and as a subsequent response to major contingencies of the local environment. Empirically, we analyzed a longitudinal dataset consisting of 3555 IJVs in China from 1999 to 2003, and found strong support for both sets of hypotheses. Product innovation in IJVs is positively associated with initial conditions such as balanced ownership structure, state partnership, and project size; IJVs are more innovative when they operate in an industry with a faster pace of innovation or a higher level of foreign direct investment legitimization, and where they are located in a region with greater agglomerated innovative activities.